PERAN KELEMBAGAAN LOKAL DALAM PENGELOLAAN PERIKANAN DI ERA DESENTRALISASI - Mustaqim, Mustaqim - (JSSH (Jurnal Sains Sosial dan Humaniora), 2018)
Abstract. The purpose of this research is to analyze the role of Panglima Laot in the management of fishery resources in Sabang Island. To be able to understand the fisheries management that involves the role of the community in the form of local institutions, a series in-depth interview, observation, as well as literature were successfully carried out to local fishery community. Since this study is a combination of qualitative and quantitative method, the data collection was analysed using phenomenological approach and critical interpretation process to see the validity and reliability of the research findings. Referring to previous research evidence, the results show that the presence of Panglima Laot has played an important role in providing information, invitation, supervision and participation in the management of fishery resources. In addition, the role of Panglima Laot in the management of fishery resources includes carrying out customs, assisting the government, resolving conflicts in the community, preventing illegal fishing, preserving the coastal environment and fighting for the living standards of fishermen is very influential both in centralization and decentralization era. Therefore, these findings can be categorized as a useful information for any party working in field of fishery program.